Light Trapping with Dielectric Scatterers in Single‐ and Tandem‐Junction Organic Solar Cells. Issue 12 (19th July 2013) - Tang, Zheng; Elfwing, Anders; Bergqvist, Jonas; Tress, Wolfgang; Inganäs, Olle
<x xml:space="preserve">Abstract</x> Efficient dielectric scatterers based on a mixture of TiO2 nanoparticles and polydimethylsiloxane are demonstrated for light trapping in semitransparent organic solar cells. An improvement of 80% in the photocurrent of an optimized semitransparent solar cell is achieved with the dielectric scatterer with ≈100% diffuse reflectance for wavelengths larger than 400 nm. For a parallel tandem solar cell, the dielectric scatterer generates 20% more photocurrent compared with a silver mirror beneath the cell; for a series tandem solar cell, the dielectric scatterer can be used as a photocurrent balancer between the subcells with different photoabsorbing materials. The power conversion efficiency of the tandem cell in series configuration with balanced photocurrent in the subcells exceeds that of an optimized standard solar cell with a reflective electrode. The characteristics of polydimethylsiloxane, such as flexibility and the ability to stick conformably to surfaces, also remain in the dielectric scatterers, which makes the demonstrated light trapping configuration highly suitable for large scale module manufacturing of roll‐to‐roll printed organic single‐ or tandem‐junction solar cells.